Powder containing porous particles, and method for producing the same

JP2026166898APending Publication Date: 2026-10-14JGC CATALYSTS & CHEMICALS LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2025060137
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2026-10-14

Smart Images

  • Figure 2026166898000001_ABST
    Figure 2026166898000001_ABST
Patent Text Reader

Abstract

This invention aims to create a powder that achieves both fluidity in powder form and packing properties when dispersed in a dispersion medium. [Solution] The powder contains porous particles formed by the aggregation of primary particles, the primary particles consist of 98% by weight or more silica, and the powder contains composite particles with a structure in which child particles are attached around a mother particle. When the particle size distribution of the powder is measured dry, there is one peak in the number frequency, and when the particle size distribution of the powder is measured wet, there are two peaks in the number frequency, and the first equivalent circle diameter D corresponds to the peak on the larger diameter side. P1 and the second circular equivalent diameter D corresponding to the peak on the smaller diameter side P2 The ratio (D P1 / D P2 ) is in the range of 2 to 10
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to powders suitable as fillers in resin compositions. In particular, it relates to powders containing porous particles formed by the aggregation of silica particles. [Background technology]

[0002] In recent years, components of electronic devices have been formed by molding and solidifying resin compositions in which inorganic fillers are dispersed in a resin material. Electronic devices such as portable terminals are becoming increasingly dense and precise year by year, and the components that make them up are also required to be dense and precise. In order to suppress their thermal expansion, it is necessary to add a large amount of filler (i.e., high-fillness) to the resin compositions that form components such as encapsulants, underfills, and substrates. In other words, there is a need for fillers that can be incorporated into resins in the largest possible quantities.

[0003] Since the size of inorganic fillers significantly affects the performance of molded products, it is common practice to limit the content of coarse particles, which are particles with a particle size above a certain size. Coarse particles are removed from the filler to improve the particle size distribution. Furthermore, it is known that mixing inorganic particles with a volume-average particle diameter of 0.1 μm to 3 μm with fine particles with a particle size of 2 nm to 100 nm suppresses the aggregation of fillers (see, for example, Patent Document 1). In addition, it is known that by increasing the proportion of fine particles with a particle size of 1 μm or less, relatively small particles are inserted between large particles, creating a "rolling" effect that reduces rolling resistance and enables the realization of a filler with excellent fluidity (see, for example, Patent Document 2). [Prior art documents] [Patent Documents]

[0004] [Patent Document 1] Japanese Patent Publication No. 2016-079278 [Patent Document 2] Japanese Patent Publication No. 2007-051187 [Overview of the Initiative] [Problems that the invention aims to solve]

[0005] In addition to suppressing thermal expansion, porous particles are sometimes used as fillers to provide functions such as weight reduction and dielectric properties. However, because porous particles are light in weight, they have a high degree of adhesion to each other, resulting in poor fluidity as a powder. Furthermore, when dispersed in resin, they cannot be dispersed with strong force to suppress particle disintegration, resulting in the problem of being usable only at low packing rates. One requirement for achieving high packing is to improve the fluidity of the powder. Too many small particles (small particles) reduce fluidity, so from the perspective of fluidity, fewer small particles are preferable. On the other hand, to achieve high packing in resin, a powder containing particles of various particle sizes is preferable. In other words, from the perspective of high packing, a certain amount of small particles is also necessary. Therefore, the objective of the present invention is to realize a powder that achieves both fluidity as a powder and packing performance when dispersed in a dispersion medium. [Means for solving the problem]

[0006] The inventors have found that the above problem can be solved by having the powder exist as composite particles in which small particles are attached to large particles, and by having the small particles separate from the large particles in the dispersion medium. That is, composite particles are formed in which small particles are attached to the periphery of large particles. In the powder state, they exist as composite particles, and when dispersed in the dispersion medium, the small particles separate from the large particles and exist individually. In other words, the powder according to the present invention is a powder containing porous particles formed by the aggregation of primary particles, the primary particles consist of 98% by mass or more silica, the powder contains composite particles with a structure in which child particles are attached to the periphery of mother particles, when the particle size distribution of the powder is measured dry, there is one peak in the number frequency, and when the particle size distribution of the powder is measured wet, there are two peaks in the number frequency, and the first equivalent circle diameter D corresponding to the peak on the larger diameter side P1 and the second circular equivalent diameter D corresponding to the peak on the smaller diameter side P2 The ratio (D P1 / DP2 ) is in the range of 2 to 10. [Brief explanation of the drawing]

[0007] [Figure 1] This is an example showing the particle size distribution of a powder when measured using both dry and wet methods. [Modes for carrying out the invention]

[0008] The powder of the present invention contains porous particles formed by the aggregation of silica particles. Sub-particles are attached to the surface of the porous particles. Here, such particles are referred to as composite particles, and the porous particles as mother particles. The mother particles have a diameter several times larger than the sub-particles. The sub-particles are also porous particles mainly composed of silica. Both the mother and sub-particles are porous and possess appropriate water content. Because moisture is present on the surfaces of both particles, the mother and sub-particles adhere to each other through liquid bridging forces. Therefore, while they adhere in the powder, in the dispersion medium, they separate because of the presence of solvent (liquid) at the adhered portion. In other words, the higher the water absorption rate of the particles, the more easily the particles tend to adhere. While large mother particles and small sub-particles can adhere to each other, the most stable arrangement is when smaller particles adhere to larger particles. Therefore, in reality, the form in which sub-particles adhere to mother particles, i.e., composite particles, is the most likely to exist.

[0009] The powder has the following characteristics: it contains porous particles formed by the aggregation of primary particles, the primary particles are composed of 98% or more silica by mass, the powder contains composite particles with a structure in which child particles are attached to the mother particles, when the particle size distribution of the powder is measured dry, there is one peak in the number frequency, and when the particle size distribution of the powder is measured wet, there are two peaks in the number frequency, with the first equivalent circle diameter D corresponding to the peak on the larger diameter side. P1 and the second circular equivalent diameter D corresponding to the peak on the smaller diameter side P2 The ratio (D P1 / D P2 ) is in the range of 2 to 10.

[0010] Figure 1(A) shows the particle size distribution when a powder is measured using the dry method. In this distribution, because composite particles are present, there are fewer individual small particles (sub-particles). Therefore, the distribution shows fewer particles on the smaller diameter side of the peak. Figure 1(B) shows the particle size distribution when a powder is measured using the wet method. When measuring using the wet method, sub-particles separate from the mother particles, so peaks for sub-particles and mother particles appear in the distribution. The peak on the larger diameter side corresponds to the peak of mother particles, and the peak on the smaller diameter side corresponds to the peak of sub-particles. For reference, Figure 1(C) shows the particle size distribution when a powder formed by a normal spray drying method is measured using the wet method. It can be seen that particles are distributed on both the smaller and larger diameter sides of the peak. Note that because the measurement principles differ between the wet and dry methods, the values ​​on the horizontal axis (particle diameter) do not match between Figure 1(A) and Figure 1(B).

[0011] The powder of the present invention preferably consists mostly of composite particles (particles in which multiple child particles are attached to a mother particle), but mother particles and child particles may also exist individually. Composite particles are preferably present in amounts of 60% or more of the total, and more preferably 75% or more. The proportion of composite particles can be calculated, for example, from SEM images of any 100 particles.

[0012] The following describes the properties of powders containing composite particles. a) Moisture absorption rate The moisture absorption rate of a powder affects the adhesion between parent and child particles. Particles with a high moisture absorption rate exhibit strong inter-particle adhesion due to liquid crosslinking. A moisture absorption rate of 10-30% is preferable. If the moisture absorption rate is 10% or higher, the moisture content during humidity control tends to be uniform, allowing for the production of uniform composite particles. If the moisture absorption rate exceeds 30%, the moisture content of the particles becomes too high, making them prone to aggregation. Therefore, it becomes difficult to obtain the desired composite particles. In addition, the particle strength decreases, making them more susceptible to disintegration.

[0013] b) Angle of repose The angle of repose of a powder refers to the angle of the conical slope naturally formed by the powder when the powder is piled up on a flat surface, and indicates the flowability of the powder. It can be determined that the smaller the angle of repose, the higher the flowability of the powder. The angle of repose is preferably 40 degrees or less.

[0014] c) Pore structure The pore structure of the particles contained in the powder is controlled by the size and shape of the silica particles. The average particle density is preferably 0.5 to 1.7 g / cm 3 . The pore volume is preferably more than 0.1 and 1.5 or less. The average pore diameter is preferably 5 to 20 nm. The average porosity is preferably 20 to 80%.

[0015] d) Average particle diameter The average particle diameter (D50) of the powder is preferably 1 to 10 μm.

[0016] e) Average circularity of porous particles The average circularity of the porous particles, that is, the average circularity in a state where the mother particles and the child particles are separated, is 0.8 or more, preferably 0.85 or more.

[0017] The powder of the present invention is an aggregate of porous particles formed by bonding a plurality of silica particles. The shape of the silica particles may be spherical or non-spherical. If non-spherical silica particles are used, porous particles with high porosity can be obtained. The non-spherical silica particles can be formed by bonding a plurality of spherical primary particles. The porous particles formed by bonding a plurality of non-spherical particles have a network structure. The average particle diameter (average secondary particle diameter d2) of the non-spherical particles is preferably 50 to 500 nm. When the average particle diameter is within this range, the non-spherical particles are not densely packed, so that a desired pore volume can be easily obtained. For the average secondary particle diameter, the particles are observed with a scanning electron microscope, and any 100 particles are selected. For each particle, the longest diameter is measured, and the average value thereof is defined as the average secondary particle diameter.

[0018] Examples of non-spherical particles include chain-like particles formed by linking multiple primary particles, fibrous particles, and non-spherical irregularly shaped particles. Primary particles may be spherical (perfect sphere, elliptical) or irregularly shaped. Non-spherical particles preferably include chain-like particles. Chain-like particles intertwine to easily obtain porous particles with a three-dimensional network structure. Here, chain-like particles include linear particles in which primary particles are linked so as to extend in a specific direction, and non-linear particles in which primary particles are linked and extend in multiple directions (regardless of whether they are two-dimensional or three-dimensional). For linear particles, the aspect ratio (major axis / minor axis) is preferably 1.2 or greater, more preferably 1.5 or greater, and even more preferably 1.8 to 10. The aspect ratio was measured for any 100 particles using electron microscope images, and the average value was taken as the average aspect ratio.

[0019] On the other hand, non-linear particles are particles that have a branched or bent structure. It is preferable to have such branched chain particles (branched particles) and bent chain particles (bent particles). In reality, there are also particles that have both a branched and bent structure. Here, such particles are also treated as branched particles. The inclusion of branched and bent particles in the non-spherical particles increases the voids between the non-spherical particles that make up the porous silica particles.

[0020] The average particle diameter (average primary particle diameter d1) of the primary particles constituting the non-spherical particles is preferably 5 to 250 nm. The average primary particle diameter d1 is calculated using the equivalent sphere conversion formula "d = 6000 / (2.2 × SA)". Here, SA is the specific surface area [m²] of the non-spherical particles obtained by the BET method due to nitrogen adsorption. 2 [ / g], 6000 is a conversion factor, and the density of silica is 2.2 g / cm³. 3 The following was determined: If the average primary particle diameter d1 is less than 5 nm, the pore size of the resulting porous particles will be small. If it is greater than 250 nm, the pore size of the resulting porous particles will be large, and the particle strength will be low, which may cause them to disintegrate.

[0021] The ratio of the average secondary particle diameter d2 to the average primary particle diameter d1 (d2 / d1) is preferably between 1.6 and 100. Within this range, a suitable three-dimensional network structure is formed.

[0022] Porous particles may consist solely of silica particles, or they may be bound together using a binder. As a binder, silicic acid solution or hydrolyzed products of alkoxides such as TEOS (silica oligomers) can be used.

[0023] Next, a method for producing a powder containing porous silica particles will be described. First, silica particles are dispersed in water to prepare a dispersion (dispersion preparation step). This dispersion is then fed into a spray dryer equipped with an impact-type fine mist generating nozzle while continuously or intermittently applying shear force to maintain a viscosity of 8-100 mPa·s (drying step). In other words, the viscosity of the dispersion fed into the spray dryer is always within this range. Then, the spray dryer granulates the silica particles in the dispersion into spherical porous particles. In this way, dried spherical porous particles are obtained. Spray drying creates porous particles of various particle sizes. The impact-type fine mist generating nozzle further impacts the finely atomized droplets, and the ultrasonic waves during impact further atomize and granulate them, resulting in the formation of many small-particle sizes.

[0024] Next, by bringing large and small particles into contact and applying vibration, composite particles are formed in which small particles adhere to the surface of large particles. By adjusting the moisture content of the particles to an appropriate level beforehand, adhesion between particles can be promoted. Methods for adjusting the moisture content include humidification in a high-humidity atmosphere or drying by heating. Any method is acceptable for particle composite formation as long as large and small particles come into contact, but the use of bead mills or ball mills is undesirable because excessive load on the particles can cause them to disintegrate. Vibrating screens and rolling granulators can be suitably used. By applying vibrations tailored to the particles, excessive adhesion and aggregation of small particles can be suppressed (composite formation process).

[0025] The process may include steps other than those described above. For example, a step may be provided to remove small particles that exist independently after the compounding step. This manufacturing method makes it possible to obtain a powder containing composite particles.

[0026] The following describes specific embodiments of the present invention. [Example 1] 60 L of water was placed in a 150 L tank, and 8.6 kg of Aerosil-380 (Nippon Aerosil Co., Ltd.) was gradually added while stirring and thoroughly mixed. This yielded a silica dispersion of non-spherical particles (silica particle concentration 12.5 wt%). The viscosity of the dispersion at this time was 200 mPa·s. The dispersion was passed through a Dispermill (Hosokawa Micron Corporation) and supplied to the impinging type fine mist generating nozzle of a spray dryer. Spray drying was performed under the conditions of a processing rate of 60 L / Hr, air / liquid ratio = 2,100, air flow rate Mach 1.1, drying atmosphere temperature 120°C, and humidity 7.2 vol% to produce dried porous particles (moisture content 2 wt%). Using a spray dryer, particles with various particle sizes are formed. The moisture content of the dried porous particles was adjusted to 10 mass%, and compounding treatment was performed using a vibrating sieve. The powder input speed was adjusted so that powder was always present on the sieve. Coarse particles and small particles present individually were removed from the particles that passed through the sieve. This resulted in obtaining a powder containing composite particles.

[0027] The viscosity of the dispersion at the start of feeding into the spray dryer was 30 mPa·s, and the viscosity of the remaining dispersion at the end of feeding into the spray dryer was 15 mPa·s. Furthermore, 50 g of this remaining dispersion was taken and dried at 110°C for 5 hours to obtain the solid component. The sodium content in this solid component was 5 ppm or less. The raw material, Aerosil-380, consisted of chain-like particles with an average secondary particle diameter of 150 nm, including branched and bent particles, and an average primary particle diameter of 7 nm.

[0028] The physical properties of the powder containing the composite particles obtained as described above were measured and evaluated as follows. The results are shown in Table 1.

[0029] (1) Average particle size The particle size distribution of the powder was measured using a dry method with a particle size analyzer (Seishin Corporation Laser Micron Sizer LMS-3000). The average particle size (D50) was obtained from the volume frequency measurement results.

[0030] (2) Pore structure A 10g sample was placed in a crucible, dried at 300°C for 1 hour, and then cooled to room temperature in a desiccator. A 0.15g sample was placed in a glass cell, and nitrogen gas was adsorbed onto the sample while vacuum degassing using a Belsorp mini II (manufactured by Nippon Bell Co., Ltd.). After desorption, the pore volume (Vp) at a relative pressure of 0.990 was determined from the resulting adsorption isotherm. The average pore diameter was also calculated using the BJH method.

[0031] The density of the sample (silica) is 2.2 g / cm³. 3 (=0.4545cm 3 The average porosity was calculated from the pore volume (Vp) using the following formula ( / g). Average porosity (%)=Vp / (Vp+0.4545)×100

[0032] Furthermore, the particle density was determined from the pore volume (Vp) using the following formula. Particle density (g / cm 3 )=2.2×(100-average porosity) / 100

[0033] (3) Moisture absorption rate The sample was dried at 120°C for 2 hours, and then its mass was measured. Furthermore, it was left to stand in an atmosphere of 25°C and 90% humidity for 48 hours to allow it to absorb moisture. Afterward, the mass was measured again, and the moisture absorption rate was calculated using the following formula. Moisture absorption rate (%) = ((Mass after moisture absorption - Mass before moisture absorption) ÷ Mass before moisture absorption) × 100

[0034] (4)Angle of repose The angle of repose was measured using a powder tester (manufactured by Hosokawa Micron Corporation).

[0035] (5) Wet particle size distribution The sample was added to pure water with a dispersant to create a dispersion with a particle concentration of 0.05% by mass, and then irradiated with ultrasound. Using this dispersion, measurements were performed on approximately 50,000 particles using a Malvern Panalytical Morphologi 4. The distribution of equivalent circle diameter was defined as the particle size distribution.

[0036] (6) Average circularity The sample was added to pure water with a dispersant to create a dispersion with a particle concentration of 0.05% by weight, and then irradiated with ultrasound. Using this dispersion, measurements were performed on approximately 50,000 particles using a Malvern Panalytical Morphologi 4. The circularity was defined as the circumference of a circle with the same area as the projected object divided by the perimeter of the object. The average of the circularity of the measured particles was defined as the mean circularity.

[0037] (7) Filling rate during resin mixing The sample (powder) was added to epoxy resin (JER828, manufactured by Mitsubishi Chemical Corporation) and mixed using a rotation / revolution type mixer (AR-100, manufactured by Thinky Co., Ltd.) to obtain a paste. The volume percentage of particles in the paste (filling rate) was calculated using the following formula. Filling rate (%) = Particle volume Vf / (Particle volume Vf + Resin volume Vr - Particle pore size) × 100

[0038] Here, the particle volume Vf(cm 3 ) = Mass of powder used Wf (g) / Particle density ρ (g / cm³) 3 ), resin volume Vr(cm 3 ) = Mass of resin used Wr(g) / Density of resin ρr(g / cm³) 3 ), particle pore size (cm 3 ) = Mass of powder used (g) × Pore volume Vp (cm 3 The density of the resin is ρf(g / cm³). 3 ) Using a graduated cylinder, measure 10 cm 3 It was calculated by measuring the mass of [the object].

[0039] When the filling rate was set to 40% or more, samples that yielded a fluid paste were marked with ○, and those that did not yield a fluid paste were marked with ×.

[0040] [Example 2] A silica dispersion of 25 nm spherical particles was prepared by diluting water glass with water, treating it with an ion exchange resin to obtain a silica solution, and then heating this silica solution. The procedure was carried out in the same manner as in Example 1, except for the use of this dispersion, to obtain a powder containing composite particles.

[0041] [Example 3] A silica dispersion of 18 nm spherical particles was prepared by diluting water glass with water, treating it with an ion exchange resin to obtain a silica solution, and then heating this silica solution. A powder containing composite particles was obtained in the same manner as in Example 1, except that this dispersion was used.

[0042] [Comparative Example 1] Powder was obtained in the same manner as in Example 1, except that Aerosil 130 was used instead of Aerosil 380. The viscosity of the dispersion before passing through the Dispermill was 383 mPa·s, the viscosity of the dispersion after passing through the Dispermill and at the start of feeding into the spray dryer was 54 mPa·s, and the viscosity of the remaining dispersion at the end of feeding into the spray dryer was 37 mPa·s. Furthermore, the sodium content in the solid obtained by drying this remaining dispersion was 5 ppm or less. The Aerosil 130 used as a raw material consisted of chain-like particles with an average secondary particle diameter of 180 nm, including branched and bent particles, and an average primary particle diameter of 21 nm.

[0043] [Comparative Example 2] A silica dispersion of 12 nm spherical particles was prepared by diluting water glass with water, treating it with an ion exchange resin to obtain a silica solution, and then heating this silica solution. A powder was obtained in the same manner as in Example 1, except that this dispersion was used.

[0044] [Comparative Example 3] A powder was obtained in the same manner as in Example 1, except that the compounding and classification processes were omitted.

[0045] [Table 1]

Claims

1. A powder containing porous particles formed by the aggregation of silica particles, The silica particles consist of 98% by mass or more silica. The aforementioned powder contains composite particles in which child particles are attached to the periphery of a mother particle. When the particle size distribution of the aforementioned powder was measured using a dry method, there was one peak in the number frequency. When the particle size distribution of the aforementioned powder was measured using a wet method, two peaks in the number frequency were observed, and the first equivalent circle diameter D corresponding to the larger diameter peak was... P1 and the second circular equivalent diameter D corresponding to the peak on the smaller diameter side P2 The ratio (D P1 / D P2 A powder characterized in that the ratio is in the range of 2 to 10.

2. The powder according to claim 1, wherein the moisture absorption rate of the powder is 10 to 30%.

3. The powder according to claim 1, wherein the angle of repose is 40 degrees or less.

4. Average particle density is 0.5–1.7 g / cm³ 3 The powder according to claim 1.

5. Pore ​​volume (g / cm³) 3 The powder according to claim 4, wherein the ratio is greater than 0.1 and less than or equal to 1.5, the average pore size is 5 to 20 nm, and the average porosity is 20 to 80%.

6. The powder according to claim 1, wherein the average particle size (D50) of the powder is 1 to 10 μm.

7. The powder according to claim 1, wherein when the powder is dispersed in a dispersion medium, the circularity of the porous particles is 0.8 or more.

Citation Information

Patent Citations

  • Fine particle-containing composition

    JP2007051187A

  • Inorganic filler and method for producing the same, resin composition and molded article

    JP2016079278A